Shaping academia for the public good : critical reflections on the CHSRF/CIHR Chairs Program - Armstrong, Pat, 1945-; Potvin, Louise, 1957- (University of Toronto Press, 2013)
Shaping Academia for the Public Good will be a helpful resource for those interested in the potential of new research approaches to improve our healthcare system.